Enhancing oil-water flow simulation in shale reservoirs with fractal theory and meshless method - Liu, Wenbo; Zhang, Guangming (Frontiers in Environmental Science, 2023)
This paper presents a novel numerical solution method for simulating the oil and water flow in shale oil reservoirs. Unlike conventional grid-based approaches, which often encounter convergence issues, we propose a methodology that leverages fractal theory to quantify the heterogeneity of fractures. A mathematical model is developed to describe oilwater flow in shale reservoirs. The meshless weighted least squares (MWLS) method is employed to solve the oil-water flow model in fractured horizontal wells within shale oil reservoirs. Our method yields results that align well with the reference solution, while offering enhanced flexibility and convenience in selecting modeling points. Furthermore, we conduct a comprehensive analysis comparing the effects of node influence domain, initial reservoir water saturation, fracture half-length, and fracture count on reservoir production. The findings demonstrate the high accuracy and convergence capabilities of our proposed method, enabling precise prediction of production in fractured horizontal shale oil wells and facilitating effective decision-making in actual production scenarios.